A Catalase‐Like Metal‐Organic Framework Nanohybrid for O2‐Evolving Synergistic Chemoradiotherapy. Issue 26 (16th May 2019) - He, Zhimei; Huang, Xiaolin; Wang, Chen; Li, Xiangli; Liu, Yijing; Zhou, Zijian; Wang, Sheng; Zhang, Fuwu; Wang, Zhantong; Jacobson, Orit; Zhu, Jun‐Jie; Yu, Guocan; et al.
Abstract: Tumor hypoxia, the "Achilles' heel" of current cancer therapies, is indispensable to drug resistance and poor therapeutic outcomes especially for radiotherapy. Here we propose an in situ catalytic oxygenation strategy in tumor using porphyrinic metal‐organic framework (MOF)‐gold nanoparticles (AuNPs) nanohybrid as a therapeutic platform to achieve O2 ‐evolving chemoradiotherapy. The AuNPs decorated on the surface of MOF effectively stabilize the nanocomposite and serve as radiosensitizers, whereas the MOF scaffold acts as a container to encapsulate chemotherapeutic drug doxorubicin. In vitro and in vivo studies verify that the catalase‐like nanohybrid significantly enhances the radiotherapy effect, alleviating tumor hypoxia and achieving synergistic anticancer efficacy. This hybrid nanomaterial remarkably suppresses the tumor growth with minimized systemic toxicity, opening new horizons for the next generation of theranostic nanomedicines. Abstract : A catalase‐like nanohybrid based on AuNPs/gold(III) porphyrinic metal‐organic frameworks is fabricated for O2 self‐supported chemoradiotherapy. Such an all‐in‐one nanohybrid holds advantages of modulating tumor hypoxia, amplifying radiation effect, regulating drug release and combining chemotherapy with radiotherapy, which will be a paradigm in O2 ‐elevated radiochemotherapy that offers a novel strategy in multimodal cancer therapy.